The economics of network industries - Shy, Oz (Cambridge University Press, 2001)
This book introduces upper-level undergraduates, graduate students, and researchers to the latest developments in network economics, one of the fastest-growing fields in all industrial organization. Network industries include the Internet, e-mail, telephony, computer hardware and software, music and video players, and service operations in the banking, legal, and airlines industries among many others. The work offers an overview of the subject matter as well as investigations about specific industries.Virtually no calculus is used in the text, and each chapter ends with a series of exercises and selected references. The text may be used for both one- and two-semester courses.